Emphasizing the role of oxidative stress and Sirt-1/Nrf2 and TLR-4/NF-κB in Tamarix aphylla mediated neuroprotective potential in rotenone-induced Parkinson’s disease: In silico and in vivo study - Dalia H. Abu-Baih; Abeer H. Elmaidomy; Hesham A. Abou-Zied; Nahla Abdelghany Hussien; Manar I. Rasekh; Entesar A. Saber; Sayed Fouad El-sheikh Ali; Mostafa E. Rateb; Omnia Magdy Hendawy; Faisal H. Altemani; Abdullah H. Altemani; Gerhard Bringmann; et al. (PLoS ONE, 2026)
Parkinson’s disease (PD) presents as a progressive deterioration of dopaminergic neurons, a process closely associated with increased oxidative damage due to accumulated reactive oxygen species, leading to weakened antioxidant defenses and ultimately neuronal dysfunction. Currently, no definitive approach exists to counteract the degeneration of dopaminergic neurons in PD. The use of Tamarix aphylla as a protective agent against Parkinson’s disease is not well studied yet. In this study, a rotenone-induced rodent model was utilized to examine the neuroprotective potential of T. aphylla extract. The chemical composition of T. aphylla leaves was analyzed through LC-HR-ESI-MS profiling, identifying 13 metabolites from various chemical categories. Furthermore, the research incorporated the STRING database and Cytoscape software to perform a protein-protein interaction (PPI) analysis, pinpointing essential hub proteins involved in neuroprotection and inflammation in PD. Molecular docking and a 150 ns molecular dynamics simulation were performed to assess the interaction of plant-derived compounds with the Sirt-1 catalytic domain. Compound 12 , one of the bioactive compounds found in T. aphylla , exhibited strong binding affinity and stability throughout the 150 ns simulation, highlighting its role as a neuroprotective agent. This study underscores the fusion of computational and experimental techniques to investigate natural neuroprotective compounds, providing potential therapeutic strategies for PD treatment by influencing key pathways linked to oxidative damage and neuroinflammation.